FUNCTIONAL AND PRAGMATIC ASPECT OF LEXICAL AND SEMANTIC MEANS OF REPRESENTATION OF SPANISH FASHION BRANDS - Asaievych, Iryna (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2025)
The article investigates the functions of lexical and semantic means in the representation of Spanish fashion brands in the publicistic discourse of Spain. It analyses the functions of terminology in the linguistic context with positive connotations, as well as the influence of stylistic means on the formation of the brands' image and attraction of the target audience. With the help of functional-pragmatic analysis, the study examines the peculiarities of the functioning of lexical and semantic fields, metaphors and epithets that modify the perception of the brand by the mass audience. The pragmatic functions of such linguistic units include the creation of brand associations with luxury, style, modernity and accessibility.  It has been found that the use of elements of popular culture, in particular references to famous personalities and mass culture, contributes to the identification of brands with a trend.  ____________References:• Kravets, L. V. (n.d.). Publitsystychnyi styl. Entsyklopediia Suchasnoi Ukrainy. Retrieved from https://esu.com.ua/article-882781• Levytska, I. M. (2014). Manipuliatsiia u mizhospopystisnii vzaiemodii: poniattia ta zmist. Visnyk Natsionalnoho universytetu oborony Ukrainy, (6)43, 312–316.• Popova, N. M. (2014). Struktura ta funktsii kohnityvnykh metafor u movnii kartyni svitu Ispanii. Visnyk, (47)2, 189–195.• Selivanova, O. O. (2008). Suchasna linhvistyka: napriamy ta problemy: Pidruchnyk. Poltava: Dovkillia-K.• Holowtschak, N., & Kuschnirtschuk, O. (2022). Funktional-stilistische Besonderheiten der deutschen texte der Publizistik (der Modus des Verbs). Suchasni doslidzhennia z inozemnoi filolohii, 21-22(3-4), 17–26.• LibreTexts Español. (n.d.). 2: Funciones y Teorías de la Comunicación de Masas. Retrieved from https://espanol.libretexts.org/Ciencias_Sociales/Ciencias_Sociales/Estudios_ de_Comunicacion/Introducción_a_la_Comunicación/La_comunicación_en_el_mundo_real_-_Una_introducción_a_los_estudios_de_comunicación/15:_Medios,_Tecnología_y_Comunicación/15.02:_Funciones_y_Teorías_de_la_Comunicación_de_Masas• España, V. (n.d.). Bimba y Lola: todo sobre la firma, la historia del talento familiar al éxito global. Vogue España. Retrieved from https://www.vogue.es/articulos/bimba-y-lola-historia-marca-familiar-exito-global• España, V. (n.d.). Pull & Bear: todo sobre la marca de moda accesible del grupo Inditex con espíritu juvenil. Vogue España. Retrieved from https://www.vogue.es/articulos/pull-and-bear-todo-sobre-la-marca-del-grupo-inditex• I. P. (n.d.). Massimo Dutti coquetea con el lujo y renueva su retail. Modaes | Noticias del negocio de la moda. Retrieved from https://www.modaes.com/empresa/massimo-dutti-coquetea-con-el-lujo-y-renueva-su-retail-con-mas-experiencia• Gamo, A. (n.d.). Hablemos de las primeras tendencias del verano que han llegado a Stradivarius. Glamour España. Retrieved from https://www.glamour.es/articulos/tendencias-verano-stradivarius• Phillips, N. (n.d.). El jersey de la colección de Rosalía para Pull&Bear demuestra que también con frío se puede ir perfecta. Vogue España. Retrieved from https://www.vogue.es/moda/tendencias/articulos/como-combinar-jersey-cuello-vuelto-pull-and-bear-coleccion-rosalia/37593• Riaño, P. (n.d.). Zara: la estrella de Inditex, al menor ritmo desde 2018. Modaes | Noticias del negocio de la moda. Retrieved from https://www.modaes.com/empresa/hablemos-de-zara-la-estrella-de-inditex-al-menor-ritmo-desde-2018
Keywords: lexical and semantic means, publicistic discourse, Spanish fashion brands, stylistic means, functional and pragmatic analysis